2001
DOI: 10.2337/diabetes.50.2007.s64
|View full text |Cite
|
Sign up to set email alerts
|

beta-cell apoptosis and defense mechanisms: lessons from type 1 diabetes.

Abstract: Increased evidence suggests that apoptosis is the main mode of ␤-cell death in early type 1 diabetes. Cytokines mediate ␤-cell apoptosis, and in this article, we discuss some of the cytokine-modified genes that may contribute to ␤-cell survival or death. The gene encoding for the inducible form of nitric oxide synthase is induced by interleukin (IL)-1␤ or IL-1␤ plus ␥-interferon in rodent and human islets, respectively. This leads to nitric oxide (NO) formation, which contributes to a major extent to ␤-cell ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 63 publications
4
112
1
3
Order By: Relevance
“…10 It has been suggested that b-cells do not remain passive to the immune attack, and that survival mechanisms are activated, among them replication, in response to injury. 35 Thus, the degree of b-cell destruction and the eventual development of type I diabetes can be determined by the balance between b-cell damage and death, and b-cell defense and growth. The demonstration that IL-1b specifically reduces b-cell replication suggests that IL-1b may play a dual role in b-cell mass reduction in type I diabetes inducing, on the one hand, b-cell death and, on the other, precluding b-cell compensatory replication.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has been suggested that b-cells do not remain passive to the immune attack, and that survival mechanisms are activated, among them replication, in response to injury. 35 Thus, the degree of b-cell destruction and the eventual development of type I diabetes can be determined by the balance between b-cell damage and death, and b-cell defense and growth. The demonstration that IL-1b specifically reduces b-cell replication suggests that IL-1b may play a dual role in b-cell mass reduction in type I diabetes inducing, on the one hand, b-cell death and, on the other, precluding b-cell compensatory replication.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is also an important feature of beta cell death in type 1 diabetes, and a recent review of experimental data concluded that immunological, inflammatory and metabolic signals combine to cause it [37]. If, for example, in vitro cytokine toxicity is increased in a hyperglycaemic milieu [38], the slow self-perpetuating beta cell destruction proposed by the Steno group should be accelerated by overload.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…1 Although T cells are central to the mechanism of beta-cell destructions, 2-5 a critical involvement of other cellular and humoral components of adaptive and innate immune system have also been demonstrated. 1,[6][7][8] Among environmental factors, infectious agents such as viruses primarily sensed by innate immune mechanisms are considered very potent triggers of T1D. [9][10][11][12] Notably, and in this context, several recently published findings suggest a strong link between T1D and enteroviral infections.…”
Section: Introductionmentioning
confidence: 99%